Pengaruh Padat Tebar Ikan Lele Terhadap Laju Pertumbuhan dan Survival Rate Pada Sistem Akuaponik [ The Effect Of Stocking Density On Survival Rate and Grow Rate Of Aquaponic System] - Boedi Setya Rahardja; Ongky Wijaya; Prayogo Prayogo (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
AbstractIncreasing consumption of catfish and dairy products encourage increased domestic production of catfish. During the period of 5 years (2005-2009), catfish production has been increased significantly with an average annual growth reached 32%. In 2008 production reached 114.371 tonnes and in 2009 production increased by almost 75% to about 200 thousand tons. Aquaponic is a bio-integration that links recirculating aquaculture principles to the production of crops / vegetables hydroponically (Diver, 2006). Aquaponic technology has proven to successfully produce an optimal fish on less land and limited water resources, including in urban areas (Ahmad, 2007). This study aims to find out the influences of catfish stocking density difference on the growth rate and survival rate of catfish on aquaponic. The experimental design used was completely randomized design (CRD). Analysis of the data processed using Analysis of Variance (ANOVA) to know whether there is influance the growth rate and survival rate between the treatment given. If there are significantly difference then proceed by Duncan's Multiple Range Test. Based on the research obtained the result that there are significant differences in the survival rate (p> 0.01) and there is a significant difference to the rate of growth (p> 0,01). From the results of statistical tests that have been done show that the highest survival rate is in treatment 4 (87.5333%) and the highest growth rate is in treatment 4 (30.5333%). The lowest Survival found in treatment 1 (53.134%). Lowest growth rate found in treatment 1 (16.6%).